MEDICAL TEXTILES: SIGNIFICANCE AND FUTURE PROSPECT IN BANGLADESH - Shilpi Akter; Abu Yousuf Mohammad Anwarul Azim; Md. Abdullah Al Faruque (European Scientific Journal, ESJ, 2014)
Now-a-days textiles are used in different sectors and various purposesbeyond imagination. Medical sector is one of them. An important andemerging part of the textile industry is medical, hygiene and health sector.The development is taking place due to the simultaneous expansion andimprovement of technology in both textile as well as medical sector. Thenumber of applications is huge and diverse, ranging from a single threadsuture to the complex composite structures for bone replacement and fromthe simple cleaning wipe to advanced barrier fabrics used in OperationTheater. The main object of this work is to study the types of medical textilesused in the medical sector, information on imported items and scope ofmanufacturing these items in Bangladesh. For this work we have visitedDhaka Medical College, Sir Salimullah Medical College, Uttara AdhunikMedical College and Hospital, BMA Bhaban Surgical Market. We havegathered very useful and vast knowledge about the term "Medical Textiles",as per our work and capability.